2020
DOI: 10.1186/s13601-020-00337-8
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated histone H3, a marker of extracellular trap formation, is increased in blood of stable asthma patients

Abstract: Background: Emerging data indicates that extracellular traps (ETs), structures formed by various immune cell types, may contribute to the pathology of noninfectious inflammatory diseases. Histone hypercitrullination is an important step in ETs formation and citrullinated histone H3 (H3cit) is considered a novel and specific biomarker of that process. In the present study we have evaluated circulating H3cit in stable asthmatics and investigated its relationship with asthma severity, pulmonary function and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…Flow cytometry analysis of NETosis markers citrullinated histone H3 (CitH3) ( 53 , 54 ) and histone H2A family member X (H2AX) ( 55 , 56 ) revealed that rEIII is sufficient to initiate NETosis in neutrophils; the potency of rEIII is comparable to the classical NETosis inducer phorbol ester ( 18 , 57 ) ( Figure 1A , Supplementary Figure 1 , flow cytometry gating; Figure 1B ). In addition, such induction of NETosis can be suppressed by treatments of inflammasome/caspase 1 inhibitor Z-WHED-FMK ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry analysis of NETosis markers citrullinated histone H3 (CitH3) ( 53 , 54 ) and histone H2A family member X (H2AX) ( 55 , 56 ) revealed that rEIII is sufficient to initiate NETosis in neutrophils; the potency of rEIII is comparable to the classical NETosis inducer phorbol ester ( 18 , 57 ) ( Figure 1A , Supplementary Figure 1 , flow cytometry gating; Figure 1B ). In addition, such induction of NETosis can be suppressed by treatments of inflammasome/caspase 1 inhibitor Z-WHED-FMK ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting H3K27me3 demethylation by a selective inhibitor GSK-J4 could improve the typical hallmarks of asthma, including airway inflammation, hyperresponsiveness, and remodeling, then alleviate the development of asthmatic disease ( 155 ). A study showed an elevated circulating H3cit level in stable asthmatics which is related to the enhanced lung extracellular traps (ETs) ( 25 ).…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…The level of citrullinated histone H3 significantly increases after LPS stimulation in macrophages derived from U937 cells in vitro , as a result of the enhanced expression level of peptidylarginine deiminases ( 121 ). The involvement of histone H3 citrullination in epigenetic regulation or gene expression has not been thoroughly studied, but it has been demonstrated to be an important step in the formation of extracellular traps for immune cells ( 122 ).…”
Section: Other Histone Posttranslational Modificationsmentioning
confidence: 99%